A New View of the 'Edesö Wreck': identifying the Swedish naval vessel Bodekull, built 1659–1661 and sunk 1678 from written sources. (18th April 2018) - Eriksson, Niklas
Abstract: This article complements the archaeological account of the so‐called 'Edesö Wreck' with archival research that has led to its identification. In 1659 the Swedish King Karl X Gustav ordered a number of vessels for transport of horses and soldiers while at war with Denmark. The king died just a few months later, the war with Denmark was aborted, and the unfinished vessels were rebuilt to serve other purposes. One of these was Bodekull, built under English master shipwright Thomas Day between 1659 and 1661. In October 1678 Bodekull sank in the Stockholm archipelago. Alterations made during construction mentioned in written sources have been noted on the wreck and strengthen the argument for the identification.